Numerical Simulation of Hot Stamping Forming of AZ Series Magnesium Alloys and Optimization of Die Process - Fang Qian (Journal of Chemistry)
In order to deal with the bottleneck of poor plasticity and low formability of magnesium alloys at room temperature, a numerical simulation and a die process optimization method based on hot stamping of AZ series magnesium alloys were proposed. Firstly, based on the PAM-STAMP finite element analysis platform, the thermomechanical coupling numerical simulation is carried out for the cross cup-shaped deep drawing, and the changes in the stress and temperature field during the forming process are analyzed. Aiming at the influence of various process parameters on the plastic formability of magnesium alloys, the effects of sheet metal shape, die fillet size, friction factor, and blank holder force on the forming quality were analyzed through experiments. The experimental results show that under the same conditions such as temperature and blank holder force, the numerical simulation method and the mold process optimized in this paper can be used to form parts that are 25% deeper than the traditional process, and the sheet material can be thinned to the maximum at this time. The amount is 0.152 mm, which verifies the correctness and superiority of the method and process in this paper.